2013
DOI: 10.1038/nn.3323
|View full text |Cite
|
Sign up to set email alerts
|

Fear and panic in humans with bilateral amygdala damage

Abstract: Decades of research have highlighted the amygdala’s influential role in fear. Surprisingly, we found that inhalation of 35% CO2 evoked not only fear, but also panic attacks, in three rare patients with bilateral amygdala damage. These results indicate that the amygdala is not required for fear and panic, and make an important distinction between fear triggered by external threats from the environment versus fear triggered internally by CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
186
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(216 citation statements)
references
References 24 publications
(34 reference statements)
14
186
1
8
Order By: Relevance
“…The BLA is one key region particularly associated with anxiety and mood (Feinstein et al, 2013;Valentino et al, 1993). The BLA receives noradrenergic input from the LC (Asan, 1998;Fallon et al, 1978) and sends projections to the CeA, the prefrontal cortex, nucleus accumbens, and BNST, regions linked to mood regulation, and some with very disparate effects (Tye and Deisseroth, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BLA is one key region particularly associated with anxiety and mood (Feinstein et al, 2013;Valentino et al, 1993). The BLA receives noradrenergic input from the LC (Asan, 1998;Fallon et al, 1978) and sends projections to the CeA, the prefrontal cortex, nucleus accumbens, and BNST, regions linked to mood regulation, and some with very disparate effects (Tye and Deisseroth, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The basolateral nucleus of the amygdala (BLA) is one key region associated with anxiety behavior (Valentino et al, 1993), including humans (Feinstein et al, 2013). We know that, in rodents, βAR antagonists infused into the amygdala block fear memory enhancement following stressful stimuli Mantsch et al, 2010;Quirarte et al, 1998;Schmidt and Weinshenker, 2014;Vranjkovic et al, 2014); is required for fear conditioning behavior (Cahill et al, 1994;Dębiec and Ledoux, 2004;Rogan et al, 1997); and systemic administration of the βAR antagonist propranolol reduces the spontaneous firing rate of neurons within the BLA (Buffalari and Grace, 2007;Ferry et al, 1997;Huang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…To further explore this issue, we tested two additional patients (AM and BG), monozygotic twin sisters with focal bilateral amygdala lesions resulting from Urbach-Wiethe disease [...] As with patient SM, both patients also reported experiencing fear during the CO 2 challenge." (Feinstein et al, 2013) These startling observations affirm that the reaction to carbon dioxide must be due to an alternative alarm system, such as has been proposed for possible suffocation. We have suggested that under conditions of threatened asphyxia the activation of the HPA system would produce a counterproductive hyperoxidative state and is therefore inactivated.…”
Section: Panic and Comorbid Conditionsmentioning
confidence: 85%
“…Further damage to the amygdalocentric fear system theory is provided by Feinstein et al (2013) who studied three patients with amygdala damage produced by Urbach-Wiethe syndrome. It is worth extensive citation:…”
Section: Panic and Comorbid Conditionsmentioning
confidence: 99%
“…Els pacients d'una malaltia rara, la síndrome d'Urbach-Wiethe, que causa la calcifi cació de l'amígdala als dos hemisferis cerebrals, han confi rmat aquesta idea. Aquestes persones mostren una absència de respostes de por a tots els estímuls experimentats (Feinstein i altres, 2011) excepte a la inhalació de diòxid de carboni (Feinstein i altres, 2013 en la seua vida. Per tant, les dades sobre el paper de l'amígdala en les memòries emocionals derivades dels experiments amb animals semblen extrapolables als humans.…”
Section: La Base Neural De Les Memòries Emocionalsunclassified